Geomagnetic control of the midlatitude foF1 and foF2 long‐term variations: Recent observations in Europe. Issue 7 (28th July 2016) - Perrone, L.; Mikhailov, A. V.
Abstract: A new very simple method, allowing an easy control, has been applied to extract long‐term (11 year) δ fo F 2 11y and δ fo F 1 11y variations from June fo F 2 and fo F 1 monthly median observations at European Slough/Chilton and Juliusruh stations, including recent data until 2015. The aim of the analysis was to check the validity of the geomagnetic control of fo F 2 and fo F 1 long‐term variations in the 21st century with the main accent on the period including the last deep solar minimum in 2008–2009. The geomagnetic control was shown to be valid. Moreover, the dependence on geomagnetic activity has become more pronounced and explicit after 1990. A simultaneous analysis of fo F 2 and fo F 1 long‐term variations improves the reliability of the obtained conclusions and helps understand the physical mechanism of these variations. Due to common neutral composition and the similarity of photochemical processes noontime fo F 2 and fo F 1 demonstrate similar long‐term variations: the correlation coefficient between δ foF 2 11y and δ fo F 1 11y is 0.834 at Slough/Chilton and 0.884 at Juliusruh with the 99% confidence level according to Fisher's F criterion. Midnight long‐term δ fo F 2 11y variations also manifest a pronounced dependence on Ap 11y which may be interpreted in the framework of the geomagnetic control concept. Key Points: The long‐term trends in the ionosphere have a natural origin The geomagnetic control of the fo F 2 and fo F 1 long‐term variations is still valid in the 21st century A simultaneous analysis of fo F 2 and fo F 1 long‐term variations helps understand physical mechanisms of these variations